Grammar Gone Astray: Language Structure Evaluation on The IELTS Writing Task One by EFL Students - Syahputra, Fikry; Panggabean, Hanna Maria; Vo, Thi Thanh Tam; Hia, Nadia Virdhani (TALENTA, 2026)
This study investigates the grammatical errors in the IELTS Writing Task One made by Indonesian EFL students. The research aims to enhance student’s comprehension and assist teachers in improving instructional approaches. The data were collected and analyzed qualitatively based on the frameworks by Chuang & Nesi and Vo. Findings revealed that grammatical errors were predominant, accounting for 88% of the total errors, with verb forms, noun errors, and pronoun errors being the most frequent. The study highlights the need for targeted instructional interventions to improve language proficiency and accuracy in the IELTS writing among Indonesian college students. These findings suggest that detailed attention to grammatical instruction and practice can significantly enhance student’s writing performance.